2022
DOI: 10.3390/pharmaceutics14051000
|View full text |Cite
|
Sign up to set email alerts
|

D-Alpha-Tocopheryl Poly(ethylene Glycol 1000) Succinate-Coated Manganese-Zinc Ferrite Nanomaterials for a Dual-Mode Magnetic Resonance Imaging Contrast Agent and Hyperthermia Treatments

Abstract: Manganese-zinc ferrite (MZF) is known as high-performance magnetic material and has been used in many fields and development. In the biomedical applications, the biocompatible MZF formulation attracted much attention. In this study, water-soluble amphiphilic vitamin E (TPGS, d-alpha-tocopheryl poly(ethylene glycol 1000) succinate) formulated MZF nanoparticles were synthesized to serve as both a magnetic resonance imaging (MRI) contrast agent and a vehicle for creating magnetically induced hyperthermia against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The europium-free sample had an r 2 /r 1 ratio of 152 which decreased to 11.2 for x = 0.15. Furthermore, manganese-zinc ferrite displayed a dual-contrast capacity, exhibiting higher longitudinal relaxivity (35.22 s −1 mM Fe −1 ) and transverse relaxivity (237.94 s −1 mM Fe −1 ) compared to Resovist ® [47]. The PEG-coated Mn, Zn ferrite NPs having a hierarchical structure and an average dimension of about 20 nm can be deemed as a promising T 2 MRI contrast agent [48].…”
Section: Mixed Oxides As Contrasts Agentsmentioning
confidence: 99%
“…The europium-free sample had an r 2 /r 1 ratio of 152 which decreased to 11.2 for x = 0.15. Furthermore, manganese-zinc ferrite displayed a dual-contrast capacity, exhibiting higher longitudinal relaxivity (35.22 s −1 mM Fe −1 ) and transverse relaxivity (237.94 s −1 mM Fe −1 ) compared to Resovist ® [47]. The PEG-coated Mn, Zn ferrite NPs having a hierarchical structure and an average dimension of about 20 nm can be deemed as a promising T 2 MRI contrast agent [48].…”
Section: Mixed Oxides As Contrasts Agentsmentioning
confidence: 99%
“…The Mn-Zn ferrite nanostructures including Mn and Zn codoped magnetite nanosystems have exhibited excellent biocompatibility, potentially exceptional magnetic properties and more importantly, an outstanding magnetic hyperthermia performance for practical applications. [97][98][99][100][101][102][103] In this section, we primarily discuss the morphological aspects, magnetic properties and hyperthermic potential, including in vivo studies based on mice-models, of Mn-Zn ferrite-based nanostructures. These nanomaterials exhibiting different morphologies that can be synthesized using the various techniques depicted in Fig.…”
Section: Mn-zn Ferrite Nanostructures For Mht Applicationsmentioning
confidence: 99%
“…105 In addition to Mn doping, it has been observed that surfactants like oleic acid or polyethylene glycol (PEG) strongly influence the shape anisotropy, magnetic properties, and self-heating abilities for magnetic hyperthermia applications of Mn-Zn ferrite-based nanomaterials. 100 In a recent study, Lin Wang et al 98 reported the fabrication of water-soluble amphiphilic vitamin E (d-alpha-tocopheryl polyethylene glycol 1000 succinate) functionalized Mn-Zn ferrite nanoparticles, denoted MZF@TPGS, as a potential candidate in cancer theranostics. Doped zinc ferrite nanostructures of varying Mn concentrations were synthesized using a thermal decomposition method, the TEM image of one such Mn-Zn ferrite nano system, Mn 0.5 Zn 0.5 Fe 2 O 4 (MZF), shown in Fig.…”
Section: Mn-zn Ferrite Nanostructures For Mht Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] In some cases, the MRI contrast agent is the therapeutic agent itself, as it is the case for gadolinium-based (Gd-based) radiosensitizing agents 11,12 or for iron magnetic particles inducing hyperthermia under an external alternating magnetic field. 13,14 Regardless of the mechanism of action of these theranostic agents, measurement of their tissue concentration is necessary to assess their therapeutic efficacy and their safety regarding healthy tissue. Assuming that the longitudinal relaxivity (r 1 ) of these MRI theranostic agents is known, their concentration can be derived from the changes in T 1 values induced by their administration to the patient or the animal.…”
mentioning
confidence: 99%